2014
DOI: 10.1021/es403941h
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Microcalorimetry Provides New Insight into Terrestrial Carbon Cycling

Abstract: Energy is continuously transformed in environmental systems through the metabolic activities of living organisms, but little is known about the relationship between the two. In this study, we tested the hypothesis that microbial energetics are controlled by microbial community composition in terrestrial ecosystems. We determined the functional diversity profiles of the soil biota (i.e., multiple substrate-induced respiration and microbial energetics) in soils from an arable ecosystem with contrasting long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Microbes metabolize a wide variety of compounds to satisfy heterotrophic demands for carbon (C) and energy, thereby influencing the accumulation/loss dynamics of soil organic matter stocks and ecosystem carbon dioxide efflux (Frey et al 2013;Karhu et al 2014). CUE is therefore an important concept for understanding the future trajectory of soil-climate feedbacks, recognition of which has led to recent reviews of the topic (Manzoni et al 2012;Sinsabaugh et al 2013), application in ecosystem models (Wang et al 2013;Allison 2014;Wieder et al 2014), and the development of new methods to estimate microbial efficiency in environmental samples (Blazewicz and Schwartz 2011;Dijkstra et al 2011b;Herrmann et al 2014). However, progress in this field is hampered by chronic issues symptomatic of a divide among research approaches and disciplinespecific terminologies.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes metabolize a wide variety of compounds to satisfy heterotrophic demands for carbon (C) and energy, thereby influencing the accumulation/loss dynamics of soil organic matter stocks and ecosystem carbon dioxide efflux (Frey et al 2013;Karhu et al 2014). CUE is therefore an important concept for understanding the future trajectory of soil-climate feedbacks, recognition of which has led to recent reviews of the topic (Manzoni et al 2012;Sinsabaugh et al 2013), application in ecosystem models (Wang et al 2013;Allison 2014;Wieder et al 2014), and the development of new methods to estimate microbial efficiency in environmental samples (Blazewicz and Schwartz 2011;Dijkstra et al 2011b;Herrmann et al 2014). However, progress in this field is hampered by chronic issues symptomatic of a divide among research approaches and disciplinespecific terminologies.…”
Section: Introductionmentioning
confidence: 99%
“…This partitioning is often referred 47 to as substrate use efficiency or C use efficiency, and it is an important microbial physiological feature in 48 determining the fate of C during organic matter decomposition in soils. This property is often assumed to be 49 constant in process-based models, but research indicates that substrate use efficiency is (i) temperature dependent 50 Recent research suggests that differences in substrate use efficiencies may be linked to the relative 58 abundance of fungi and Gram-negative bacteria in an arable ecosystem (Harris et al 2012;Herrmann et al 2014) or 59 a forest ecosystem (Creamer et al 2015). These studies emphasize that microbial community composition may play 60 a significant role in determining substrate use efficiencies within one land use management system.…”
Section: Introduction 41mentioning
confidence: 99%
“…Isothermal calorimetry measures the net outcome of heat flows derived from all catabolic and anabolic reactions in soils; it quantifies all microbial metabolic processes, not only those accounted for by CO 2 respiration measurements. Recent research (Herrmann et al, 2014) therefore has demonstrated that such an approach is a more comprehensive methodology, providing complementary information for investigating soil microbial metabolism than the respiratory approach alone. Although very little is known about the link between soil microbial energetics and CO 2 respiration, changes in calorespirometric ratios may indicate differences in microbial C use efficiencies and metabolic pathways (Hansen et al, 2004;Herrmann et al, 2014) or a change in organic material undergoing decomposition (Hansen et al, 2004).…”
mentioning
confidence: 99%
“…Recent research (Herrmann et al, 2014) therefore has demonstrated that such an approach is a more comprehensive methodology, providing complementary information for investigating soil microbial metabolism than the respiratory approach alone. Although very little is known about the link between soil microbial energetics and CO 2 respiration, changes in calorespirometric ratios may indicate differences in microbial C use efficiencies and metabolic pathways (Hansen et al, 2004;Herrmann et al, 2014) or a change in organic material undergoing decomposition (Hansen et al, 2004). However, respiration and microbial energetics are often obtained by separate samples and methods (Sparling, 1983;Herrmann et al, 2014) which often results in highly varying calorespirometric ratios.…”
mentioning
confidence: 99%